Innovating in education: effectiveness of PBL on students' skills - Neves, Ana Catarina Moiteiro das (2016)
The purpose of this study was to assess the impact of project-based learning on students’ motivation and critical thinking, considering the importance of preparing students for a knowledge-based economy. The research analysed 113 students from four schools were the project Mentes Empreendoras was implemented. Pre and post-test analyses and a matching procedure were conducted to guarantee comparability. The study suggests positive evidences of project-based learning in the motivation and critical thinking skills of students, indicating that an educational approach that fosters self-discovery might be well suited to engage and motivate students and promote their critical thinking.